ANALISIS YURIDIS PENERAPAN PASAL 112 AYAT (1) DAN AYAT (2) DIKAITKAN DENGAN PENERAPAN PASAL 127 AYAT (1) HURUF A, AYAT (2), DAN AYAT (3) UNDANG-UNDANG NOMOR 35 TAHUN 2009 TENTANG NARKOTIKA DALAM MEMBERIKAN KEPASTIAN HUKUM DI INDONESIA - Jhon Nover Siburian; Mukhlis R; Syaifullah Yophi (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2023)
The criminal provisions in the current narcotics law, namely Law number 35 of 2009, it isclosely related to the formulation of actions committed by someone in connection with these narcotics.Penal provisions began to be regulated in CHAPTER XV from Article 111 to Article 148 of Law No.35 of 2009 . In narcotics cases, there are several articles that are often used to ensnare perpetrators,one of which is Article 112 and Article 127 paragraph (1) letter a of Law No. 35 of 2009 concerningNarcotics. The two articles, which have multiple interpretations and unclear formulation, namelyArticle 112 and Article 127 paragraph (1) letter a of Law No. 35 of 2009 concerning Narcotics.The objectives in writing this thesis are: First , to find out the judge's considerations in applyingArticle 112 and Article 127 of Law Number 35 Years 2009 About Narcotics. Second, To find out LegalCertainty in the Application of Article 112 and Article 127 of Law Number 35 Years 2009 AboutNarcotics. The type of research used in this research is normative legal research. In this normativeresearch the authors conducted research on legal principles .From the results of the study it was found that the judge's judgment in applying Article 112 andArticle 127 of Law Number 35 Year 2009 concerning Narcotics is that the judge's decision in acriminal case of narcotics abuse is not always the same, even in the same case the results of thedecisions are different, this is what is referred to as a disparity decision, where the judge decides onthe same case but with a different decision . Legal certainty in Article 112 and Article 127 of theNarcotics Law it can be said that the articles it still does not provide a legal certainty. it is becauseredaction of articles that are still multi-interpreted and contain double meanings. Author'sSuggestion, First, It is hoped that the panel of judges will give more consideration to therehabilitation aspect for narcotics users (not dealers) compared to prison sentence decisions becausethe obligation of rehabilitation is more needed for narcotics addicts . Second, make changes to theNarcotics Law, especially to Article 112. This change is really needed considering the increasingnumber of perpetrators narcotics crime that should have been charged with Article 112 but wascharged using Article 127 .Keywords: Narcotics-Legal Certainty- Criminal Acts